Соображения о мессианстве библейском, иудейском, христианском и секулярном (в частности, о России) [Isidor Levin. On Biblical, Jewish, Christian, and Secular Messianism] - Левин, Исидор (Hyperboreus, 2011)
The paper examines messianic expectations and ideas through the ages, from their beginning in the period of the First Temple through the later Jewish religious movements, to the rise of Christianity and to the Modern era. It includes short biographies of pseudo-Messiahs within the Diaspora in the Middle Ages and Early Modern period and concludes with an analysis of messianic ideas in modern Judaism.